Analisis Wacana Guru Bhakti dalam Cerita Bhagawan Dhomya: Kuasa Pengetahuan dan Hegemoni Guru kepada Ketiga Muridnya - Adnyana, Putu Eka Sura (Institut Hindu Dharma Denpasar, 2020)
Bhagawan Domyaâ€™s story is one episode in the Adiparwa text, which tells about the obedience of the three students to a teacher. In this story a teacher tests the devotions and devotion of his students, namely is Arunika, Utamanyu, and Veda. The story is discussed with the discourse theory from Michel Foucault. The data is taken from the Adiparwa book by Zoetmulder, to be precise abaout Bhagawan Dhomyaâ€™s story. Data analusis is the process of examining all research data obtained through observation, recording, documents, and so on. The results of this study will be presented using an informal method because the data studied is qualitative data in the from of verval narrative. Foucaultâ€™s discourse in the Adiparwa text on Bhagawant Dhomya went testing his three students using the discourse of guru bhakti, then Bhagawan Dhomya can exercise his power over his three students by carrying out â€œpinariksaâ€ test as a from of his hegemony, as well as the basis for giving his gift of knowledge to his three students.